How Movie Events Engage Childrens' Brains to Combine Visual Attention with Domain-Specific Processing Involving Number and Theory of Mind in a Cinematic Arena. Issue 1 (1st March 2022) - Levin, Daniel T.; Mattarella-Micke, Andrew; Lee, Madison J.; Baker, Lewis J.; Bezdek, Matthew A.; McCandliss, Bruce D.
Abstract: Using functional magnetic resonance imaging, we tested the hypothesis that cinematic structure shapes variation in social-cognitive brain activity. Using our film, we completed an exploratory analysis of how activations in the temporal-parietal junction (TPJ), and the intraparietal sulcus (IPS) are shaped by variations in insert shots (e.g., shots showing objects that a character has looked at), and by character entrances and exits. We found that IPS and TPJ consistently responded to insert shots, and the correlation between TPJ and IPS responses significantly predicted the prevalence of belief inferences during the sequence. In addition, TPJ responded significantly to entrances and exits of characters. We also completed a qualitative analysis of moments during a sequence that induced relative peaks in TPJ and IPS responding. These analyses not only demonstrate that consistent brain responses can distinguish among meaningful variations in cinematic events but also that these analyses confirm and refine our understanding of the apparent specializations for visual attention and domain-specific event processing in parietal attention networks.